The Importance of Amine-degrading Enzymes on the Biogenic Amine Degradation in Fermented Foods: A review. (December 2020) - Li, Binbin; Lu, Shiling
Highlights: Traditional fermented foods are receiving more attention in food quality and safety. Enzymatic degradation of biogenic amines in fermented foods and beverages is a promising strategy. The development and diversity of amine-degrading enzymes are described and discussed. Multicopper oxidases are superior to other amine-degrading enzymes in BAs degradation. Limited applications of amine-degrading enzymes in fermented foods and beverages. Abstract: Biogenic amines (BAs) are a class of harmful compounds often be found in high protein foods, especially naturally fermented foods. BAs derive from free amino acid decarboxylation through microbial activities and can cause toxic effects (headache, heart palpitations, vomiting) on humans, depending on individual sensitivity. Indigenous amine-degrading strains or strains producing amine-degrading enzymes (ADEs) have drawn great attention since they play an important role in affecting BA accumulation, and enzymes/genes involved in the biosynthetic mechanisms. They also help maintain the sensory quality of the final products. Besides, due to ADEs' harmless catalytic products, they can be further utilized in fermented foods and beverages to reduce BAs. This review describes in detail the mechanisms of BAs formation, as well as the diversity of ADEs able to degrade BAs in a model or real food systems. A deeper knowledge of this issue is crucial because ADEs' activities are often associated with strains rather than species or genera. Moreover, this information can help to improve the selection and characterization of strains for further applications as starters or bioprotective cultures, to obtain high-quality foods with reduced BAs contents.